New CuO nanocomposite as non-enzymatic glucose biosensor - Mojtaba Ghorbani; Aliakbar Tarlani; saeed Taghvaei-Ganjali; Mercede Malekzade (Nanomedicine Journal)
Objective(s): In a new approach, copper(II) oxide (CuO) nanostructure was synthesized by a solvothermal method for applying as a biosensor for detecting of glucose. Determination of the glucose is important in controlling of diabetes. Non-enzymatic detection of glucose is preferable because of its low cost benefits. Otherwise, CuO can play a role in oxidation of glucose to gluconic acid which is important in glucose detection. Therefore, obtaining new morphology or new composite from CuO is interesting. Materials and Methods: CuO nanostructure was prepared with the assistance of a bifunctional amino acid of L-lysine (with the isoelectric point about 10 for precipitating copper ion) and an additive of urea. Fourier transform infrared (FT-IR) and Raman spectroscopies, X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), cyclic voltammetry analyses and differential pulse voltammetry (DPV) were employed.Results: XRD indicated that the synthesized CuO consists of a tenorite crystal system with a monoclinic structure. The TEM histogram showed a mean diameter of 91 nm for CuO nanostructure. CuO nanostructure loaded on graphene oxide-grafted Lisdexamfetamine Dimesylate (LIS) to achieve CuO/LIS-g-GO composite. CuO/LIS-g-GO was dropped on a glassy carbon electrode (GCE) to develop a new nanobiosensor for detecting glucose in a cost-effective manner without the necessity of using glucose oxidase or nafion. Phosphate buffer (PBS) and simulated body fluid (SBF) solutions were the media of the glucose detection. The sensitivity of the biosensor was 34.7 µA/cm2mM for 10 mM concentration of the glucose. The mentioned sensor detected no interference in the presence of dopamine and fructose. Also, the repeatability of the biosensor was investigated and the measured standard deviation (RSD) was 3.93%.Conclusion: New nanostructured CuO was composited with LIS-g-GO and the new biosensor of CuO/LIS-g-GO/GCE was applied for the detection of glucose. The sensitivity of 34.7 µA/cm2mM without any interference of dopamine and fructose caused this system as favorite sensor for the detection of glucose.